Stromal cells of the mouse spleen - Den Haan, Joke M.; Mebius, Reina; Kraal, Georg (Frontiers in Immunology, 2012)
The composition and function of stromal cells in the white pulp of the spleen resemble to a large extent the situation in other secondary lymphoid organs such as lymph nodes. The stromal cells play an important role in the support and guidance of lymphocytes and myeloid cells in the T and B cell zones of the spleen. Major differences of the spleen are found in the way cells enter the white pulp and the composition of stromal cells in the red pulp. In this review, the features of stromal cells of both white and red pulp will be described in light of the function of the spleen.